5-HT1A receptors in the dorsal hippocampus mediate the anxiogenic effect induced by the stimulation of 5-HT neurons in the median raphe nucleus - Santos, Lucinéia dos [UNESP]; Andrade, Telma Gonçalves Carneiro Spera de [UNESP]; Junior, Helio Zangrossi (Elsevier B.V., 2008)
We evaluated the involvement of dorsal hippocampus (DH) 5-HT1A receptors in the mediation of the behavioral effects caused by the pharmacological manipulation of 5-HT neurons in the median raphe nucleus (MRN). To this end, we used the rat elevated T-maze test of anxiety. The results showed that intra-DH injection of the 5-HT1A/7 agonist 8-OH-DPAT facilitated inhibitory avoidance, an anxiogenic effect, without affecting escape. Microinjection of the 5-HT1A antagonist WAY-100635 was ineffective. In the elevated T-maze, inhibitory avoidance and escape have been related to generalized anxiety and panic disorders, respectively. Intra-MRN administration of the excitatory aminoacid kainic acid, which non-selectively stimulates 5-HT neurons in this brain area facilitated inhibitory avoidance and impaired escape performance, but also affected locomotion. Intra-MRN injection of WAY-100635, which has a disinhibitory effect on the activity of 5-HT neurons in this midbrain area, only facilitated inhibitory avoidance. Preadministration of WAY-100635 into the DH blocked the behavioral effect of intra-MRN injection of WAY-100635, but not of kainic acid. These results indicate that DH 5-HT1A receptors mediate the anxiogenic effect induced by the selective stimulation of 5-HT neurons in the MRN. (c) 2007 Elsevier B.V. and ECNP. All rights reserved.
Keywords: median raphe nucleus; dorsal hippocampus; 5-HT1A receptors; serotonin; generalized anxiety and panic